Effect of Foreign Direct Investment (FDI) on economic growth and labor absorption in Maluku - Fahrudin Ramly; D. Rumerung; Rukmuin Wilda Payapo (Institute of Computer Science (IOCS), 2023)
This study aims to determine the effect of foreign direct investment (FDI) on economic growth and employment. Method, for this purpose, secondary data was collected in the form of annual data from the Central Bureau of Statistics and the Investment and One-Stop Integrated Service (PTSP) Office of Maluku Province. The data were analyzed using simple linear regression. The analysis model used adopts the Cobb Douglas function, namely Q = f (A Kα Lβ) with the assumption that Q is economic growth, K is capital and L is labor and A is technological progress. In the case of this study, it is assumed that economic growth is a function of capital, namely foreign investment (FDI) so that by modifying the Cobb-Douglas production function. The results showed that foreign investment (FDI) has a positive and significant effect on economic growth and employment. The effect of foreign investment (FDI) has a positive and significant effect on economic growth in Maluku Province. Policies that make it difficult for investors need to be reduced. Investment also has an influence on employment. Realized investment can expand production capacity and that will require additional labor.